A Contrastive Analysis Between English and Karonese Language on Question Word - Cici Ajah Ika; Herman; Dumaris E. Silalahi (Scholars Digest Publishing, 2022)
This study discusses the contrastive analysis of pronoun analysis for questions from English to Karo language. This study aims to analyze the differences and similarities of pronouns in English and Karo language. To analyze this research using a qualitative type of research with documentation techniques. Collection by reading some references related to the learning material. The data that has been collected can be qualified to solve research problems. After analysis, the study found similarities in the two languages : relative pronoun in English from karoness has the same position in a sentence, can in the form of , after the subject or before the object. Relative pronoun dslam English and Karo language have the same form. Si can be used as a subject, object, preposition and possessive for people and things. The result of this research is to show the similarity of the form of language specifically when a person or a social group igin conducts questions and answers to other individual members and to find out how the structure of language in language questions with other languages.
Keywords: Students’ learning outcomes, Objective Questions, Subjective Questions, Surface learning , Deep learning